LEGAL INNOVATION POLICY FOR FREE TRADE AREA (A STUDY OF FREE TRADE AREA IN CHINA) - Isharyanto, Isharyanto (PRANATA HUKUM, 2024)
The rise of Free Trade Zones (FTZs) led by China marks a significant trend in the global economy. This study explores the legal validity of novel policies within Chinese FTZs; how legitimate are these policies? It assesses how FTZ policies align with national and global trade regulations by analyzing legislative frameworks, policy documents, and international treaties. Results show that China's legal advancements in FTZs, which feature regulatory streamlining and improved foreign investment practices, generally align with global standards but sometimes conflict with domestic regulations. These advancements are bolstered by targeted economic legislation designed to stimulate growth and test reforms for possible nationwide implementation. Furthermore, the study highlights FTZs as hubs for international trade and arenas for economic experimentation. The conclusion offers policy suggestions to strengthen the legal basis and global alignment of FTZ innovations, ensuring they effectively contribute to economic development.